Visual Outcomes After Descemet Membrane Endothelial Keratoplasty Versus Descemet Stripping Automated Endothelial Keratoplasty—Comparison of Specific Matched Pairs. Issue 6 (June 2016) - Droutsas, Konstantinos; Lazaridis, Apostolos; Papaconstantinou, Dimitrios; Brouzas, Dimitrios; Moschos, Marilita M.; Schulze, Stephan; Sekundo, Walter
Abstract : Purpose: To compare visual rehabilitation after Descemet membrane endothelial keratoplasty (DMEK) and Descemet stripping automated endothelial keratoplasty (DSAEK) for Fuchs endothelial dystrophy. Methods: The medical records of patients undergoing endothelial keratoplasty were retrospectively evaluated. A DMEK (n = 25 eyes) and a DSAEK (n = 25 eyes) group were formed. Specific matched pairs consisting of 1 DMEK and 1 DSAEK eye with the same preoperative best spectacle-corrected visual acuity (BSCVA) were built and compared with regard to visual rehabilitation, subjective refraction, central corneal thickness, and endothelial cell density. Results: Preoperative median BSCVA (logarithm of the minimal angle of resolution) was for both groups 0.7 (range, 0.2–1.70). At 12 months, median BSCVA was 0.0 (range, −0.08 to 0.7) after DMEK and 0.3 (range, 0.1–0.52) after DSAEK ( P < 0.001). The spherical equivalent changed after DMEK from 0.0 D (range, −2.75 to 4.63 D) to 0.5 D (range, −1 to 2.5 D) and after DSAEK from −0.32 D (range, −2.50 to 1 D) to 0.63 D (range, −2.38 to 2 D). Central corneal thickness decreased from 718 μm (range, 566–1041 μm) to 533 μm (range, 460–605 μm) after DMEK and from 650 μm (range, 527–749 μm) to 605 μm (range, 486–650 μm) after DSAEK. Endothelial cell density decreased from 2448 cells/mm 2 (range, 2106–3000 cells/mm 2 ) to 1263 cells/mm 2 (range, 589–2282 cells/mm 2 ) after DMEK and from 2348 cells/mm 2 (range, 2156–2781 cells/mm 2 ) to 1327 cells/mm 2 (range, 664–1972 cells/mm 2 ) after DSAEK. Conclusions: DMEK patients showed faster rehabilitation and higher BSCVA at all postoperative visits; however, the decline in graft's endothelial cell count and change in the spherical equivalent were similar for both procedures.